Analysis of a multiband monopole handset antenna combined with a slotted ground plane. Issue 1 (20th November 2012) - Picher, C.; Anguera, J.; Bujalance, A.; Andújar, A.; Puente, C.
Abstract The ground plane of a handset device plays an important role in the radiation process. As a consequence, through a ground plane modification, it is possible to obtain a multiband performance while keeping small antenna dimensions. Numerical simulation using Method of Moments has been used to understand the effect of the slots and a prototype has been built to validate the solution. The proposal consists in a multiband planar monopole handset antenna featuring a small area of 13 mm × 11 mm with a slotted ground plane operating in multiple communication standards (GSM850, GSM900, DCS, PCS, UMTS, LTE2300, WiMAX, Bluetooth, and Wi‐Fi). Thanks to the presence of the slots, the bandwidth and efficiency results have been significantly improved. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:173–180, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27232